2018
DOI: 10.1111/ecaf.12321
|View full text |Cite
|
Sign up to set email alerts
|

M‐Pesa and the ‘Market‐Led’ Approach to Financial Inclusion

Abstract: Inclusive financial systems play a critical role in fostering economic growth and development. However, the question of what is the best means of achieving this has long been a puzzle. In this article, I use the mobile money revolution in Sub‐Saharan Africa to show that the greatest examples of financial development have come from nations embracing a market‐led approach that removes repressive regulations and gives entrepreneurs the freedom to discover innovative ways to access the unbanked. Comparing the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Alampay et al, 2017), or "…unlock significant economic opportunity and accelerate social development" (Ding et al, 2018: 20). Similarly, Manacorda and Tesei (2016) refer to mobile phones as 'liberation technologies' and 'mobile money' has been labelled a 'revolution' (Burns, 2018;Jack and Suri, 2014) -what Maurer (2012) calls an 'empowerment narrative'.…”
Section: Fintech and 'Development' In Poorer Countries: Last-mover Admentioning
confidence: 99%
See 2 more Smart Citations
“…Alampay et al, 2017), or "…unlock significant economic opportunity and accelerate social development" (Ding et al, 2018: 20). Similarly, Manacorda and Tesei (2016) refer to mobile phones as 'liberation technologies' and 'mobile money' has been labelled a 'revolution' (Burns, 2018;Jack and Suri, 2014) -what Maurer (2012) calls an 'empowerment narrative'.…”
Section: Fintech and 'Development' In Poorer Countries: Last-mover Admentioning
confidence: 99%
“…remittances and other private cash transfers) (World Bank, 2017). Definitions of 'financial inclusion' vary, such as expanding the ratio of the population that has access to formal financial services (Burns, 2018), delivering sustainable and useful financial services at affordable costs to disadvantaged and low-income people (Kim et al, 2018), or even the broader condition of financial regulations to ensure customers' finances are adequately protected against risk (World Bank, 2017).…”
Section: Fintech and 'Development' In Poorer Countries: Last-mover Admentioning
confidence: 99%
See 1 more Smart Citation
“…Microfinance schemes are not only useful financing options, but important tools for economic empowerment and social change, particularly for women [23,27,[34][35][36][37]. For instance, the authors in [37] surveyed 840 women beneficiaries of microfinance in Ghana and concluded that about 72% of the respondents reported being better financially resourced to provide the educational, health, and basic needs of their families.…”
Section: Impacts and Challenges Of Mobile Money Andmentioning
confidence: 99%
“…On the supply side, as mentioned the penetration of bank accounts is low, particularly in rural areas, but adoption of M-PESA is widespread. Kenya is even often presented as "the poster child that 'digital payments can make the world a better place" [13]; see also [14] (p. 412).…”
Section: Introductionmentioning
confidence: 99%